2013
DOI: 10.1155/2013/342571
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Performance following Carotid Endarterectomy or Stenting in Asymptomatic Patients with Severe ICA Stenosis

Abstract: Background. Endarterectomy (CEA) or stenting (CAS) of a stenotic carotid artery is currently undertaken to reduce stroke risk. In addition removal of the arterial narrowing has been hypothesized to improve cerebral hemodynamics and provide benefits in cognitive functions, by supposedly resolving a “hypoperfusion” condition. Methods. In this study we sought to test whether resolution of a carotid stenosis is followed by measurable changes in cognitive functions in 22 subjects with “asymptomatic” stenosis. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…Grunwald et al [37] have also shown cognitive improvements in both word fluency and in delayed recall when under neuropsychological testing that was conducted 24 h after internal carotid artery stenting in asymptomatic patients. Results in asymptomatic patients similar to those outlined above have also been published by Wang et al [30] and Picchetto et al [38] .…”
Section: Carotid Endarterectomy An Old Approach In An Endovascular Ersupporting
confidence: 86%
See 1 more Smart Citation
“…Grunwald et al [37] have also shown cognitive improvements in both word fluency and in delayed recall when under neuropsychological testing that was conducted 24 h after internal carotid artery stenting in asymptomatic patients. Results in asymptomatic patients similar to those outlined above have also been published by Wang et al [30] and Picchetto et al [38] .…”
Section: Carotid Endarterectomy An Old Approach In An Endovascular Ersupporting
confidence: 86%
“…Therapeutic effects of stenting do exist and is has shown to be superior to that observed by medical prescriptions including selective serotonin reuptake inhibitors in these patient groups. However, in a study by Picchetto et al [38] , it was observed that there was no difference amongst pre-and post-scoring in the neuropsychological evaluation of both depression and anxiety carried out in asymptomatic internal carotid artery stenosis patients who received stenting.…”
Section: Carotid Endarterectomy An Old Approach In An Endovascular Ermentioning
confidence: 92%
“…Picchetto et al 20 observed significant improvement in RAVLT performance after carotid interventions, and Lal et al 4 reported an overall improvement in cognitive performance, but no significant differences between the CAS and CEA groups, whereas others suggest no cognitive change 21,22 or decline in cognition. 23,24 We have also assessed multiple cognitive domains, but we chose to focus on RAVLT as our primary cognitive measure because it has been identified to be sensitive in detecting changes after carotid interventions.…”
Section: Discussionmentioning
confidence: 99%
“…There also needs to be further study of the neural substrates of functional improvements and resilience. For example with respect to memory, there are some studies that find declines ( Aharon-Peretz et al, 2003 ; Heyer et al, 1998 ; Zhou et al, 2012 ) but an increasing number of studies demonstrate improvements or resilience against the lesions ( Aleksic et al, 2006 ; Bossema et al, 2005 ; Crawley et al, 2000 ; Ghogawala et al, 2013 ; Incalzi et al, 1997 ; Kim et al, 2015 ; Kougias et al, 2015 ; Kuliha et al, 2015 ; Migliara et al, 2013 ; Mononen et al, 1990 ; Ortega et al, 2014 ; Pearson et al, 2003 ; Piccetto et al, 2013 ; Takahashi et al, 2013 ; Wang et al, 2015 ; Xia et al, 2015 ; Xu et al, 2007 ; Zhou et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%